Artificial Intelligence (AI), labor relations and human resource management - Almeida, F.; Junça Silva, A.; Lopes, S. L.; Ricardo, S. (Challenges and opportunities in the artificial intelligence era, 2025)
This chapter explores the evolution of human resource management (HRM), highlighting the shift from an administrative function to a strategic role driven by technology, culminating in algorithmic management. Algorithmic management, which uses algorithms and artificial intelligence (AI) for workforce-related decisions, offers advantages such as increased efficiency and data-driven decisions, but also presents significant challenges, including lack of transparency and dehumanization. The chapter addresses the ethical and legal issues associated with this practice, including algorithmic biases, privacy concerns, job security, and the impact on workplace relationships. Ultimately, algorithmic management has the potential to positively transform labor relations, provided it is implemented responsibly, with attention to equity, transparency, and respect for workers’ rights.